2022
DOI: 10.3389/fpls.2021.807514
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of the PMEI Gene Family in Tea Plant and Functional Analysis of CsPMEI2 and CsPMEI4 Through Ectopic Overexpression

Abstract: Pectin methylesterase inhibitor (PMEI) inhibits pectin methylesterase (PME) activity at post-translation level, which plays core roles in vegetative and reproductive processes and various stress responses of plants. However, the roles of PMEIs in tea plant are still undiscovered. Herein, a total of 51 CsPMEIs genes were identified from tea plant genome. CsPMEI1-4 transcripts were varied in different tea plant tissues and regulated by various treatments, including biotic and abiotic stresses, sugar treatments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…MdPMEI3 encodes a pectin esterase inhibitor that regulates the demethylation of pectin in apical meristematic tissues, thereby influencing protoplast formation and foliar structure patterns ( Lionetti et al., 2007 ). Overexpression of AtPMEI3 has been shown to promote HG hypermethylation and influences the formation of floral primordia ( Li et al., 2021 ). The hub gene MdFTSHC , detected in the “MEblue” module, is an ATP-dependent zinc metalloprotease containing an AAA (an ATPase associated with various cellular activities) and a Zn 2+ metalloprotease structural domain that plays a key role in the hydrolysis of membrane proteins ( Adam et al., 2005 ; Wagner et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…MdPMEI3 encodes a pectin esterase inhibitor that regulates the demethylation of pectin in apical meristematic tissues, thereby influencing protoplast formation and foliar structure patterns ( Lionetti et al., 2007 ). Overexpression of AtPMEI3 has been shown to promote HG hypermethylation and influences the formation of floral primordia ( Li et al., 2021 ). The hub gene MdFTSHC , detected in the “MEblue” module, is an ATP-dependent zinc metalloprotease containing an AAA (an ATPase associated with various cellular activities) and a Zn 2+ metalloprotease structural domain that plays a key role in the hydrolysis of membrane proteins ( Adam et al., 2005 ; Wagner et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…PPME , pectinesterase-like PMEs ( PECTIN METHYLESTERASE INHIBITORs ) maintains apoplastic Ca 2+ -homeostasis, controlling stomatal movements and in regulating the flexibility of the guard cell wall ( Wu et al., 2018 ). Previous studies have also suggested that inhibiting the pectin methylesterase activity of tea plants, including Pectin Methylesterase Inhibitor 2 and 4 ( CsPMEI2 and CsPMEI4 ), slightly reduces the cold tolerance of transgenic Arabidopsis ( Li et al., 2021 ). XTHs (Xyloglucan endotransglucosylase/hydrolase) cuts and re-joins hemicellulose chains in Plant cell wall, contributing to wall assembly, affecting cellulose deposition ( Wu et al., 2018 ).…”
Section: Regulatory Mechanisms Of Cold Tolerance Of Tea Plantsmentioning
confidence: 99%
“…Both CsCaM1 and CsCML7, 15, 21, 35, and 55 were highly expressed after 7 d of low-temperature stress. CsCML1, 4,25,33,36,37,40,41,43,44,50,56, and 57 showed the highest expression level after the de-acclimation (DA) treatment. However, the rest of the genes showed no expression in response to cold treatment.…”
Section: Expression Patterns Of Cscam and Cscml Genes Under Abiotic S...mentioning
confidence: 99%
“…The tea plant (Camellia sinensis) is an evergreen economic plant that grows well in normal temperature, high humidity, and acid soil (pH 4.5-5.5) environments [43]. However, due to the recent occurrence of extreme weather events, the tea plant typically cannot overwinter safely or grow healthily when damaged by drought, heat, salinity, low temperature, or cold spells.…”
Section: Introductionmentioning
confidence: 99%